The Book of Time - Guillaume Prevost (U.S.A,India Scholastics, 2006)
A statue; a coin; an old book. They look as dusty as everything else in the Faulkner Antiquarian Bookstore, where 14-year-old Sam Faulkner seeks his father, who's been missing for days. But when Sam slips the coin into the statue, he's swept back in time -- to Scotland in 800 A.D. -- where he must find both the statue and another coin in order to return to the present. It's the first step in an adventure that will take him to ancient Egypt, World War I, even Dracula's castle -- and a mystery that will end only when Sam saves his father, or loses him in time . . .
Keywords: Science Fiction -- Science Fiction; Fantasy -- Fantasy